The Crusade to Ban Books. - Arons, Stephen (Education Digest, 1981)
This article focuses on the censorship on the books, which deal with Jews, black or Hispanics, in the American schools. A nationwide survey sponsored by the Association of American Publishers (AAP), the American Library Association, and the Association for Supervision and Curriculum Development indicates that the nation is in the midst of a surge of book censorship which seems designed to cut off independent thought at its educational roots. Nearly 2,000 responses from 7,500 public school administrators and librarians point to the involvement of over 20 percent of the nation's school districts and 30 percent of its school libraries in challenges to literary works and textbooks. Unfortunately, the AAP report understates the magnitude of the movement to ban books. Attempted book censorship in school and public libraries has continued at a record rate with the rising fortunes of the New Right. Casualties are mounting. Attacks have already succeeded against works by several scholars. Publishers, civil libertarians, and school organizations are looking more carefully at how excessive pressure can destroy the delicate balance of interests that makes majority control of schools tolerable to the minority.